Implementation Science. - Ruppar, Todd M. (Western Journal of Nursing Research, 2026)
The article focuses on the importance of implementation science in nursing research to bridge the gap between evidence-based interventions and their adoption in clinical practice. Implementation science studies the factors influencing the integration and sustainability of interventions in real-world healthcare settings and encourages incorporating implementation considerations early in the research process. Nurse scientists, supported by Doctor of Nursing Practice-prepared colleagues, are positioned to enhance intervention design and stakeholder engagement to improve healthcare outcomes. The article highlights growing federal funding interest in implementation science and distinguishes it from local evidence-based practice projects by its systematic research methods and measurement of implementation outcomes such as acceptability, adoption, and sustainability. It encourages nurse researchers to adopt implementation science principles to accelerate and improve the translation of research into practice.